Association between adverse clinical outcome in human disease caused by novel influenza A H7N9 virus and sustained viral shedding and emergence of antiviral resistance - Hu, Yunwen; Lu, Shuihua; Song, Zhigang; Wang, Wei; Hao, Pei; Li, Jianhua; Zhang, Xiaonan; Yen, Hui-Ling; Shi, Bisheng; Li, Tao; Guan, Wencai; Xu, Lei; et al. (The Lancet (British edition), 2013)
On March 30, a novel influenza A subtype H7N9 virus (A/H7N9) was detected in patients with severe respiratory disease in eastern China. Virological factors associated with a poor clinical outcome for this virus remain unclear. We quantified the viral load and analysed antiviral resistance mutations in specimens from patients with A/H7N9. We studied 14 patients with A/H7N9 disease admitted to the Shanghai Public Health Clinical Centre (SPHCC), China, between April 4, and April 20, 2013, who were given antiviral treatment (oseltamivir or peramivir) for less than 2 days before admission. We investigated the viral load in throat, stool, serum, and urine specimens obtained sequentially from these patients. We also sequenced viral RNA from these specimens to study the mutations associated with resistance to neuraminidase inhibitors and their association with disease outcome. All patients developed pneumonia, seven of them required mechanical ventilation, and three of them further deteriorated to become dependent on extracorporeal membrane oxygenation (ECMO), two of whom died. Antiviral treatment was associated with a reduction of viral load in throat swab specimens in 11 surviving patients. Three patients with persistently high viral load in the throat in spite of antiviral therapy became ECMO dependent. An Arg292Lys mutation in the virus neuraminidase (NA) gene known to confer resistance to both zanamivir and oseltamivir was identified in two of these patients, both also received corticosteroid treatment. In one of them, wild-type sequence Arg292 was noted 2 days after start of antiviral treatment, and the resistant mutant Lys292 dominated 9 days after start of treatment. Reduction of viral load following antiviral treatment correlated with improved outcome. Emergence of NA Arg292Lys mutation in two patients who also received corticosteroid treatment led to treatment failure and a poor clinical outcome. The emergence of antiviral resistance in A/H7N9 viruses, especially in patients receiving corticosteroid therapy, is concerning, needs to be closely monitored, and considered in pandemic preparedness planning. National Megaprojects of China for Infectious Diseases, Shanghai Municipal Health and Family Planning Commission, the National Key Basic Research Program of China, Ministry of Science and Technology, and National Natural Science Foundation of China.